Analysis of Digital Learning Media "Typing Land" to the Reading Ability at Kak Seto School - Maryani, Kristiana; Rosidah, Laily; Mutia Yuzandi, Zahra (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This study aims to analyze the reading ability of students at Kak Seto School and determine the effectiveness of digital learning media in improving their reading skills. The study uses a qualitative approach with a case study design, focusing on three first-grade students at Kak Seto School who cannot read. Data is collected through observation, documentation, and interviews with teachers from the TIK (Technology of Information and Communication) department. The study's findings indicate that the students have a common problem: Sensory Processing Disorder, and that digital learning media can effectively improve their reading abilities. The research implications and limitations of the study are that it focuses only on three students at Kak Seto School, and the findings may not be generalizable to other schools or contexts. However, the study has practical implications for teachers, who must proactively introduce children to letters and train their learning abilities. The use of digital media can facilitate critical thinking and problem-solving skills, which are essential for academic success. The originality and value of this study lie in its contribution to understanding the role of digital learning media in improving reading abilities in children. The study provides important insights into the benefits of digital media in teaching and learning and highlights the need for further research. By utilizing digital media effectively, educators can help enhance the reading abilities of students struggling to learn in traditional classroom settings. Overall, this study has important implications for educators, policymakers, and parents interested in improving children's literacy rates.